Facing the Challenge of Post COVID-19 Pulmonary fibrosis: What is so unique about it? - Ghose, Medha; Islam, Tasbirul (Bangladesh Critical Care Journal, 2020)
COVID-19 pandemic is the highlight of the 21st century that took drastic effects on humanity. Over 23 million confirm infected with the majority with mild infection. However, over 62,000 cases are in critical condition with varying degrees of ARDS. A potential complication of severe ARDS could be Post COVID-19 Pulmonary fibrosis. Possible use of biomarkers to detect progression to fibrosis, along with prompt treatment of acute lung injury caused by COVID-19 and administration anti-fibrotic therapies, could be the next best method to treat this permanent and devastating sequela of COVID-19. Bangladesh Crit Care J September 2020; 8(2): 102-107